2022
DOI: 10.1002/brb3.2596
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits of patients with multiple sclerosis and their correlation with anxiety and depression levels: A cross‐sectional case–control study

Abstract: Objective Multiple sclerosis is a chronic demyelinating disease of the central nervous system that can cause severe disability and impair the quality of life (QoL). Methods In the current cross‐sectional, case–control study, we investigated personality traits, anxiety and depression levels, in 101 patients in the case group and 202 individuals as a control group. The personality traits of the participants were collected via the Neuroticism‐Extraversion‐Openness Five‐Factor Inventory (NEO‐FFI) questionnaire. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Our study aimed to shed light on the complex interplay between psychological factors and personality traits among pwMS. The exploration of personality traits in pwMS provides us with valuable insights into how pwMS deal with their condition and enables us to tailor their treatment strategies accordingly [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study aimed to shed light on the complex interplay between psychological factors and personality traits among pwMS. The exploration of personality traits in pwMS provides us with valuable insights into how pwMS deal with their condition and enables us to tailor their treatment strategies accordingly [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the lack of treatment adherence can negatively impact the duration and severity of their disability and disease [ 50 ]. Moreover, there is supporting evidence indicating that mood disorders are linked to the extent of disability in pwMS [ 25 ]. When considering the connection between personality traits and psychological factors, it can be inferred that there exists a correlation between disability and personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 It has also been reported that neuroticism personality trait is more dominant in MS patients and is associated with anxiety and depressive mood. [7][8][9][10] Recent studies have shown that neuroticism is associated with impaired physical disability, cognitive functioning and mental resilience. 3,11,12 Conversely, positive personality traits such as extraversion, conscientiousness and openness have been reported to be protective factors against physical and neuropsychiatric symptoms.…”
Section: Introductionmentioning
confidence: 99%